Biomass and quantitative indices of phytoplankton in Mandovi-Zuari estuary - Kumari, L Krishna; John, Julie (Indian Journal of Fisheries, 2011)
Biomass in terms of Chlorophyll a, cell density and quantitative indices of phytoplankton from two estuarine stations and a coastal station off Goa has been studied during 1997-98. Biomass in terms of Chlorophyll a averaged 1.1, 1.3 and 1.4 mg/m3 and cell density 0.72, 0.82 and 0.77 x 104 cells/l respectively at Stns. 1,2 & 3. Diatoms contributed 85.55, 95.55 and 92.22% respectively at Stns. 1,2 & 3. Contribution of dinoflagellates was about three times high at Stn 1 as compared to Stns 2 & 3. Significant difference was not observed in the quantitative indices between the stations. Attempts have been made to evaluate the interrelationship between various parameters and the role of salinity and mixing on phytoplankton biomass and diversity